The Role of Multinational Corporations in International Relations - Ana DAMASCHIN (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This research provides an overview of the most important theoretical concepts and practical issues by describing the negotiation process in the contemporary international system with multinational corporations. Thorugh the context, the author also addresses the defining role of multinational corporations in negotiations and their levers of power. The proposed novel element describes the rational bargaining model applied by multinational corporations in the context of international business negotiations, emphasizing also the influence of multinational actors on foreign policy through corridor/informal bargaining (lobbying practice).